1993
DOI: 10.1177/0148607193017004375
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Arginine‐Enriched Total Parenteral Nutrition on the Host‐Tumor Interaction in Cancer‐Bearing Rats

Abstract: By using a transplantable Yoshida sarcoma in a rat total parenteral nutrition model, we measured the effectiveness of an arginine-enriched amino acid solution (AI-82) in terms of leucine kinetics and nitrogen balance as indicators of host-tumor nutrition interaction compared with that of a conventional amino acid solution (Proteamin12). When tumor-bearing rats received isocaloric total parenteral nutrition solutions for 7 days, AI-82 significantly improved host nitrogen balance and significantly decreased the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Nutrition may in uence tumour growth since some tumours require large amounts of speci c nutrients (44), and deplete the body pool in tumour-bearing rats. Nutrients should meet host nutritional requirements but not tumour needs and therapeutic approaches should provide nutrients that improve the nutritional status of the host over that of the tumour (45,46). Therefore, the effects of GH and hyperproteic diets require further research in tumour-bearing models before their clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Nutrition may in uence tumour growth since some tumours require large amounts of speci c nutrients (44), and deplete the body pool in tumour-bearing rats. Nutrients should meet host nutritional requirements but not tumour needs and therapeutic approaches should provide nutrients that improve the nutritional status of the host over that of the tumour (45,46). Therefore, the effects of GH and hyperproteic diets require further research in tumour-bearing models before their clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…After an abdominal operation and trauma, a negative N balance with progressive loss of body protein is observed, possibly resulting from hormonal changes and cytokine secretion (Fong et al 1990;Baigrie et al 1992). A report by Oka et al (1993) showed that TPN with Arg improved the host N balance in tumour-bearing rats. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary 3-methylhistidine was determined as previously described. 15 In the second experiment (analysis of tissue DNA or RNA synthesis), groups of 24 rats and 20 rats were randomized to receive one of two intravenous diets for 2 days and 7 days, respectively. The infusion methods were the same as described earlier.…”
Section: Methodsmentioning
confidence: 99%